Conflict and Coexistence of Natural Resource Exploitation and Ancient Monument Group Conservation - Exploration of the Path of Sustainable Development - Song, Andre Xiaoyu (Transactions on Environment, Energy and Earth Sciences, 2024)
The article reviewed several impacts of conflicts between resources exploitation and heritage protection in worldwide. Infrastructure construction as a major project for developing countries with poor heritage exploration might directly expose the archeological heritage under atmosphere, and lead to severe oxidization. Fossil fuel factories will release sulfur dioxide and nitroxide into the air, and following acid deposition will harm the surrounding heritages made with marbles or wood and cost high repairing fee for the government. The destruction of minority’s heritages by mining projects also happened around the world, which brings up concerns of minority rights lost and poor supervision to the companies. The unbalanced economic growth has result to the illegal deeds like stolen or looting frequently happened in developing countries with relatively poor checking, and lead to many valuable artifacts are traded in the black markets. With plenty of concerns and difficulties in applying heritage protections, the paper has stated the potential direction for solution, which involved a long-term cooperation between local government and international archeology organization through public education to complete legislation.